Pain Evaluation and Treatment in Children: A Practical Approach - Lorenzo Sansone; Cristina Gentile; Eleonora Agata Grasso; Armando Di Ludovico; Saverio La Bella; Francesco Chiarelli; Luciana Breda (MDPI AG, 2023)
Pain is the most common complaint reported by children who access the emergency departments, but despite its frequency and the availability of many international guidelines, it often remains underreported and undertreated. Recently, the American Academy of Pediatrics and the American Pain Society have reiterated the importance of a multidisciplinary approach in order to eliminate pain in children. In all pediatric settings, an adequate assessment is the initial stage in a proper clinical approach to pain, especially in the emergency departments; therefore, an increasing number of age-related tools have been validated. A wide range of analgesic agents are currently available for pain management, and they should be tailored according to the patient's age, the drug's pharmacokinetics and the intensity of pain. In order to facilitate the choice of the appropriate drug, a treatment algorithm based on a ladder approach can be used. Moreover, non-pharmacological techniques should be considered to alleviate anxiety and distress in pediatric age. This review aims to offer a simple but intuitive description of the best strategies for pain relief in children, starting with the prompt recognition and quantification of pain through adequate assessment scales, and following with the identification of the most appropriate therapeutic choice among the ones available for pediatric age.